Dietary supplementation with sunflower seeds and vitamin E for fattening lambs improves the fatty acid profile and oxidative stability of the Longissimus lumborum - Almeida, Fabiana Alves de [UNESP]; Silva Sobrinho, Américo Garcia da [UNESP]; Manzi, Gabriela Milani [UNESP]; Lima, Natalia Ludmila Lins [UNESP]; Endo, Viviane [UNESP]; Zeola, Nivea Maria Brancacci Lopes [UNESP] (Csiro Publishing, 2015)
This study aimed to evaluate the effects of supplementation with sunflower seeds and vitamin E for fattening lambs, on the chemical composition, cholesterol, vitamin E level, fatty acid profile and lipid oxidation of meat from sheep. Four treatments were evaluated, as follows: SC - basal diet consisting of sugarcane + concentrate; SCS - basal diet supplemented with sunflower seed; SCE- basal diet supplemented with 1000 mg vitamin E; SCSE-basal diet supplemented with sunflower seed and 1000 mg vitamin E. The Longissimus lumborum muscle of 32 Ile de France lambs, which were slaughtered when their bodyweight reached 32 kg, was used. The chemical composition of the lamb meat was not significantly different (P > 0.05) between the treatments. Sunflower seed supplementation increased (P < 0.05) the levels of linoleic acid, vaccenic acid and conjugated linoleic acid. Inclusion of vitamin E in the diet increased (P < 0.05) the concentration of vitamin E in the meat while decreasing lipid oxidation. Considering the current demand for healthy foods, inclusion of sunflower seeds and vitamin E in the diet of sheep is a viable possibility.
Keywords: Lamb meat; Lipid oxidation; Oil seed; Sheep